Analisis Pengaruh Faktor Persepsi Kemudahan, Publikasi, Kenyamanan Akses Dan Kepercayaan Terhadap Minat Beli Tiket Menggunakan Aplikasi Mobile Kai Access (Studi pada pengguna aplikasi KAI Access di Garut) - Sulistyowati Sulistyowati; Anto Aryanto; Sunarno Sunarno (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2023)
The background of this research is that many users of the KAI Access mobile application complain about the difficulty of using some of the features provided, such as difficulty logging into the KAI Access mobile application, frequent loading when making payments, server down and lack of agility in making repairs, few payment options.the user interface which is considered difficult to understand to the error notification where it is not clear where the error is. This study aims to determine the effect of perceived convenience, publication, convenience of access and trust partially on purchase intention. The population in this study were users of the KAI Access mobile application and the sample for this study was 100 respondents. The sampling technique is nonprobability sampling with the type of sampling that is purposive sampling. Data analysis used in this study was descriptive analysis and quantitative analysis, data were analyzed using multiple linear regression analysis with the help of (software) Statistical Package for Social Science (SPSS) version 26. The results of research by testing the hypothesis t-test showed that perceived ease of use, publication, ease of access and trust have a positive and significant effect on purchase intention. Based on the research results, it can be seen that the research model of the multiple linear regression equation is:Y= -1.735 + 0.291.X1 + 0.256.X2 + 0.247.X3 + 0.335.X4 + μ The results of the equation show that the Perceived Convenience variable (X1) has (t count 3.442 > t table 1.984), the Publication variable (X2) has (t count 2.398 > t table 1.984), the Ease of Access variable (X3) has (t count 2.892 > t table 1.985) and the variable Trust (X4) has (t count 4.802 > t table 1.984). As for the value of Adjusted R2 = 0.619. This means that 61.9% of the variation in the dependent variable (Y), namely Purchase Intention, is explained by the independent variables, namely Perceived Convenience, Publication, Convenience of Access and Trust. The remaining 100% - 61.9% = 38.1%, other variables not proposed in this study.